Digital Platforms Are an Important Aspect of Digitalization of Higher Education - I. E. Zhukovskaya (Открытое образование (Москва))
The purpose of the study is to identify the effectiveness of the functioning of digital platforms in the information systems of higher educational institutions in order to optimize the managerial, educational, methodological, research, and innovation activities of the University for the training of highly qualified specialists. This goal is especially relevant in an environment where modern higher education institutions strive to take the most advanced positions in world and domestic university rankings. This study shows that the transition of modern higher education institutions to the category of digital poses a variety of tasks for universities, academies and institutes. Such as the quality of the educational process, optimization of university management, scientific publications in the field of digital technologies, the number of open online courses, the amount of funding for grants in the field of information and digital technologies, academic mobility, the opinions of student respondents, graduates and employers who indicated areas of “digital technology”, etc. Digital platforms currently being implemented in higher education institutions are the basis for their transition to the category of digital universities and the quality of functioning in the economic market among competitors.Materials and methods. In the course of this study and in writing the article, methods such as analysis of empirical data, synthesis, methods of questionnaire survey, logical and contextual analysis, bibliographic search, SWOT analysis, methods of working with specialized software products and web services, matching method and method of comparison, induction, deduction, monographic study were used, etc.Results. This article proves that digital platforms are the basis for the development of an innovative strategy of the university in accordance with the requirements of the digital transformation of the world economic system. In addition, the author of the article shows that digital platforms are currently one of the important components for the university to achieve the status of a “digital university”, contribute to the development of the digital infrastructure of the university, increase the level of digital competence of all participants in the educational process at the university, the possibility of using digital technologies such as the Internet of things, blockchain, machine learning and artificial intelligence, Big Data, quantum technologies, robotization, etc., which ultimately contributes to the training of highly qualified specialists for industries and sectors of the country’s economy.Conclusion. This paper reviews modern digital platforms used in various universities, identifies positive and negative aspects when working with digital platforms in higher education institutions, on the basis of which it is concluded that digital platforms are an effective assistant in the individualization and personalization of education, can be used as a simulator for teaching and testing the knowledge of students and undergraduates of universities.